eHealth Technologies Enable more Accessible Hearing Care - Swanepoel, De Wet (Seminars in Hearing, 2020)
Hearing loss is a pervasive global health care burden affecting up to one in every seven persons of whom 90% reside in low- and middle-income countries. Traditional service-delivery models are unable to support and promote accessible and affordable hearing care in these setting. Major barriers include a severe shortage of hearing health care professionals, costs associated with equipment, facilities and treatments, and centralized service-delivery models. Convergence of digital and connectivity revolutions are combining to enable new ways of delivering decentralized audiological services along the entire patient journey using integrated eHealth solutions. eHealth technologies are allowing nonprofessionals in communities (e.g., community health workers) to provide hearing services with point-of-care devices at reduced cost with remote surveillance and support by professionals. A growing body of recent evidence showcases community-based hearing care within an integrated eHealth framework that addresses some of the barriers of traditional service-delivery models at reduced cost. Future research, especially in low- and middle-income countries, must explore eHealth-supported hearing care services from detection through to treatment.
Keywords: mHealth; telehealth; audiology